PSYCHOLOGICAL POSSIBILITIES OF MODELING THE PROFESSIONAL CAREER OF YOUTH (Universal International Scientific Journal, 2026)
This scientific article analyzes the psychological possibilities of the process of modeling the professional career of young people. In modern society, the issue of choosing a profession and professional development is an important stage in the life of young people. Therefore, an in-depth study of psychological factors in this process is of urgent importance. A person's interests, motivation, abilities, values, and level of self-awareness are considered important factors in determining a professional direction. The role of psychological counseling, diagnostics, and developmental training in the process of career modeling is also highlighted.
Keywords: professional career, modeling, psychological capabilities, career choice, motivation, personal development, youth psychology.